2013
DOI: 10.1016/j.jacc.2013.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Outcomes of Side Branch Occlusion After Main Vessel Stenting in Coronary Bifurcation Lesions

Abstract: Angiographic findings of SB, proximal MV stenosis, and clinical presentation are predictive of SB occlusion after MV stenting. Occlusion of sizable SB is associated with adverse clinical outcomes..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 193 publications
(75 citation statements)
references
References 12 publications
5
68
2
Order By: Relevance
“…This higher rate of PMI may be explained by a greater percentage of branch occlusions with the subintimal approach (48.2% vs. 16.2%; p < 0.001). Whether branch occlusion-based enzyme elevation has an impact on long-term outcomes remains controversial (22,23) and was not assessed by our data due to the short follow-up of the study.…”
Section: Discussionmentioning
confidence: 90%
“…This higher rate of PMI may be explained by a greater percentage of branch occlusions with the subintimal approach (48.2% vs. 16.2%; p < 0.001). Whether branch occlusion-based enzyme elevation has an impact on long-term outcomes remains controversial (22,23) and was not assessed by our data due to the short follow-up of the study.…”
Section: Discussionmentioning
confidence: 90%
“…All cine coronary angiograms were reviewed and analyzed quantitatively at the angiographic core laboratory (Cardiac and Vascular Center, Samsung Medical Center, Seoul, Korea) with an automated edge-detection system (Centricity CA 1000; GE, Waukesha, WI). Two experienced technicians who were blinded to patient information reviewed the cine angiograms 11 ; interobserver variability was 0.81 (0.73-0.87), and intraobserver variability was 0.97 (0.97-0.98).…”
Section: Percutaneous Coronary Interventionmentioning
confidence: 99%
“…Hahn JY et al reported that the presence of a stenotic lesion at the SB and proximal MV are independent predictors of SB occlusion after MV stenting [2]. In our case, the lesion had both findings and was considered at high risk for SB occlusion.…”
Section: Discussionmentioning
confidence: 60%